The beauty of sorrow: - V. Tendenan (Acta Theologica)
This article explores the Ma’badong dance in the death rituals of the Torajan culture in Indonesia, emphasizing Gerardus van der Leeuw’s expansive definition of dance as a comprehensive expression of the human spirit. It argues that dance transcends a mere reflection of the soul, positing that sorrow in the Ma’badong danceis a manifestation of divine presence. This dance, still practiced today, embodies a theological aesthetic of “the beauty of sorrow,” examined through several dimensions. Firstly, it expresses sadness and empathy towards death. Secondly, it universalizes the human body as an instrument of sorrow. Thirdly, it celebrates life amidst grief. Fourthly, it provides a language of lamentation, creating a space for encountering God. Lastly, the Ma’badong dance affirms that God is present in the dancers’ sorrow. This article presents the Ma’badong dance as a profound theological aesthetic, where sorrowful movements become beautiful, facilitating remembrance of self, others, and God.